2018
DOI: 10.29271/jcpsp.2018.03.s66
|View full text |Cite
|
Sign up to set email alerts
|

Primary Renal Epithelioid Angiosarcoma

Abstract: Primary renal angiosarcoma is a rare tumor. Epithelioid variant of primary renal angiosarcoma is extremely rare and aggressive entity described in literature as a few case reports. It presents as solid looking renal mass as other renal cell carcinomas. Management is not well described due to scarcity of cases and aggressiveness of disease. We hereby report a case of epithelioid renal angiosarcoma in a 62-year female who presented with features of infected perinephric collection. Histopathological and immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Angiosarcoma is a malignant vascular neoplasm which may occur in any location of the body, including the skin, soft tissue, breast, bone and visceral organs including the liver. Primary renal angiosarcoma is very rare, with about 70 cases described in the literature to date [49][50][51][52][53][54][55][56][57]. Most of these cases are seen in older men, with a peak incidence in the sixth to seventh decades and a pronounced male predilection (male-to-female ratio of 7:1) [49].…”
Section: Angiosarcomamentioning
confidence: 99%
See 2 more Smart Citations
“…Angiosarcoma is a malignant vascular neoplasm which may occur in any location of the body, including the skin, soft tissue, breast, bone and visceral organs including the liver. Primary renal angiosarcoma is very rare, with about 70 cases described in the literature to date [49][50][51][52][53][54][55][56][57]. Most of these cases are seen in older men, with a peak incidence in the sixth to seventh decades and a pronounced male predilection (male-to-female ratio of 7:1) [49].…”
Section: Angiosarcomamentioning
confidence: 99%
“…CT imaging demonstrates a hypodense mass with varying levels of contrast enhancement ranging from none, to heterogeneous, to intense peripheral, to diffuse enhancement [53,54,58,59]. Central areas of necrosis or hemorrhage may be detected [55]. MRI studies have shown intermediate to high signal intensity on T1-weighted images, and some cases show alternating areas of high and low signal intensity on T2-weighted images, creating a striated pattern corresponding to alternating necrotic and solid areas of the tumor [59].…”
Section: Angiosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, primary renal epithelioid angiosarcoma; which mimics epithelial tumors, both morphologically and immunohistochemically, is an extremely rare and aggressive malignancy with a rapidly metastatic and fatal course, which presents a great diagnostic challenge as it mimics RCC, and it is associated with rapid local and bloodstream dissemination. Consequently, patients usually have advanced disease when diagnosed and a high risk for recurrence (3). Lastly, primary well-differentiated renal neuroendocrine tumors (carcinoid) area also exceedingly rare neoplasms, considered a distinct entity within the latest World Health Organization Classification scheme (4), with histological features identical to carcinoid tumors found at other anatomical locations (5).…”
mentioning
confidence: 99%
“…metastasis and tumor size (11,12). The mainstay of treatment of PRA is surgical resection (12). Sequential chemotherapy with/without radiotherapy may be applied but the survival rate remains low (13).…”
mentioning
confidence: 99%